Efficacy of conventional pharmacotherapy of syndromic management of STIs: a two year cross-sectional prospective study - Kushwah, Beenu; Kushwah, Devendra Singh (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Syndromic management has been the centre for treating STIs in a resource constraint facility since its introduction by WHO and CDC more than a decade back. Recently there has been lots of debate on its empirical use in an era of antibiotics resistance and ever-changing varieties of microorganisms causing these infections. Present study evaluated the efficacy of pharmacotherapy of syndromic management measured by symptomatic improvement in females presenting with STIs. Methods: It was a two year cross-sectional prospective study including all the females of STI syndromes, attending Gynecology OPD of Sanjay Gandhi Memorial Hospital and results were assessed in pharmacology department, Gajra Raja medical college Gwalior from Jan 2015 to December 2016. Results: During the study period total of 24,556 patients attended the Gynecology OPD out of which 8562 patients presented with different STI syndromes. Lower abdomen pain with vaginal discharge was the most common symptom while Ulcerative lesions were the least common complaint. Maximum recurrence was seen in patients of vaginal discharge and itching followed by PID syndrome which responded to second line of drugs. Conclusions: Syndromic Management of STIs is an old approach to deal with a very common gynecological problem and needs to be reviewed in an era of wide spread antibiotics resistance.